Microbial Consumption of Atmospheric Isoprene in a Temperate Forest Soil - Cleveland, C. C. (American Society for Microbiology, 1998)
Isoprene (2-methyl-1,3 butadiene) is a low-molecular-weight hydrocarbon emitted in large quantities to the atmosphere by vegetation and plays a large role in regulating atmospheric chemistry. Until now, the atmosphere has been considered the only significant sink for isoprene. However, in this study we performed both in situ and in vitro experiments with soil from a temperate forest near Ithaca, N.Y., that indicate that the soil provides a sink for atmospheric isoprene and that the consumption of isoprene is carried out by microorganisms. Consumption occurred rapidly in field chambers (672.60 ± 30.12 to 2,718.36 ± 86.40 pmol gdw(−1) day(−1)) (gdw is grams [dry weight] of soil; values are means ± standard deviations). Subsequent laboratory experiments confirmed that isoprene loss was due to biological processes: consumption was stopped by autoclaving the soil; consumption rates increased with repeated exposure to isoprene; and consumption showed a temperature response consistent with biological activity (with an optimum temperature of 30°C). Isoprene consumption was diminished under low oxygen conditions (120 ± 7.44 versus 528.36 ± 7.68 pmol gdw(−1) day(−1) under ambient O(2) concentrations) and showed a strong relationship with soil moisture. Isoprene-degrading microorganisms were isolated from the site, and abundance was calculated as 5.8 × 10(5) ± 3.2 × 10(5) cells gdw(−1). Our results indicate that soil may provide a significant biological sink for atmospheric isoprene.